Urban transformation towards university metaphor in the context of wisdom and civilization - Kayadibi, Saim (2012)
In today's globalized societies, basic phenomenon and judgments have gradually lost their influence, with technological developments almost the whole world has been reduced to a single city concept. Yet the urban culture, the understanding of living together, leaves its place to the smaller communities and even more to individualism. While wisdom and civilization were an integrated perception with the city, in the course of time this perception has been transformed shaping the mentality not where it is viewed from, however, how it is viewed. In this context, the city concept through this perception is re-opened for further discussion. In other words, the wisdom and civilization have been looked through the window of cities until the last few decades such as Mecca, Medina, Baghdad, Istanbul, Kufa, and Samarqand etc. Nevertheless, nowadays it has been more often looked from not the window of the cities, but from the window of Universities such as Oxford, Al-Azhar, Harvard, Sorbonne, Istanbul University, and International Islamic University Malaysia etc. As before, no civilization can be talked within a place where city is not exist, however, now the concept has been transformed to an understanding that wisdom and civilization cannot be talked within a place where there is no universities. In regards to this phenomenon, universities become centres for Islamic civilization to grow and flourish like cities before. Law and jurisprudence are also being transformed in connection with the city concept based on the maxim of “it is an accepted fact that the terms of law (ahkam) vary with the change in the course of times”. With this transformation process, in order to proceed firmly in line with civilizational parameters and values, there is need for help of serious mechanisms such as maqasid al-shari‘ah (higher objectives of Islamic law), siyasah al-shari‘ah (public policy of Islamic law). It’s hoped that putting these mechanisms into operation would bring substantial contributions to the perception of wisdom and civilization through the urban transformation towards university metaphor in order to flourish and grow intellectually. It could be talked neither about wisdom and civilization nor law and jurisprudence in places where there are no social communities. As a social reality that a city and law cannot achieve perfection without jurisprudence, law and jurisprudence also cannot achieve the perfection without city, how the city metaphor and civilization could then be read within the reshaping of a new globalized world. Such question would be a central point to be considered carefully by philosophers and social engineers. In this study, International Islamic University Malaysia will be taken as sample model for re-structuring wisdom and civilization in line with the transformation of city metaphor. In conjunction with this transformation, in order to proceed firmly, the serious mechanisms of maqasid al-shari‘ah (higher objectives of Islamic law), siyasah al-shari‘ah (public policy of Islamic law) will be taken into consideration. The concepts of law and jurisprudence, city and university will also be analysed within the process of creating new place for wisdom and civilization.